2004
DOI: 10.1177/8756087904050409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Erucic Acid Percentage on Slip Properties of Erucamide

Abstract: Erucamide is a fatty acid amide most frequently used to reduce the coefficient of friction (increase slip) of polyolefin films. The erucic acid content of commercial erucamides varies from 80 to 94%. A project has been initiated to determine the effect, if any, that this variation has on slip properties. The performance of erucamide is measured in: • three different butene copolymer linear low-density polyethylenes (LLDPEs) • a hexene copolymer LLDPE • three different low-density polyethylenes (LDPE) Slip is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Polymer brushes 1 are useful for many applications, such as to control interactions between nanoparticles 2 and to build functional interfaces for smart coatings; 3 they are present in cell membranes and bone cartilages, 4 as slip agents for plastic sheets 5 and in drug delivery. 6 Although most studies have been carried out for uniform polymer brushes, i.e., those made up of chains of the same length, some have been performed for brushes made up of polydisperse chains.…”
mentioning
confidence: 99%
“…Polymer brushes 1 are useful for many applications, such as to control interactions between nanoparticles 2 and to build functional interfaces for smart coatings; 3 they are present in cell membranes and bone cartilages, 4 as slip agents for plastic sheets 5 and in drug delivery. 6 Although most studies have been carried out for uniform polymer brushes, i.e., those made up of chains of the same length, some have been performed for brushes made up of polydisperse chains.…”
mentioning
confidence: 99%
“…Even more, experimental results have shown that the COF depends on the hydrocarbon chain length of the FAs 4,10 , the extrusion time 11 , the surface concentration of FAs 8,9,12 , and the aging of the sample 5,9 . One of the most popular slip agents is erucamide; this fluid-friction reducing molecule is obtained from naturally occurring fats and oils frequently used in the polymer industry [6][7][8][9]13 .…”
mentioning
confidence: 99%
“…Additives have been used for years as sliding agents to modify the tribological properties of thin films [1][2][3] . Functionalized polymethylmethacrylate (PMMA) 4 and polyolefines (POs) 3,[5][6][7][8][9] surfaces with brushes composed by fatty acids (FAs) have proved to be useful to reduce the coefficient of friction (COF) of these materials. Even more, experimental results have shown that the COF depends on the hydrocarbon chain length of the FAs 4,10 , the extrusion time 11 , the surface concentration of FAs 8,9,12 , and the aging of the sample 5,9 .…”
mentioning
confidence: 99%
See 2 more Smart Citations